2021
DOI: 10.1002/imhj.21959
|View full text |Cite
|
Sign up to set email alerts
|

When the Bough Breaks: A systematic review and meta‐analysis of mental health symptoms in mothers of young children during the COVID‐19 pandemic

Abstract: Parents have experienced considerable challenges and stress during the COVID-19 pandemic, which may impact their well-being. This meta-analysis sought to identify: 1) the prevalence of depression and anxiety in parents of young children (< age 5) during the COVID-19 pandemic, and 2) sociodemographic (e.g., parent age, minority status) and methodological moderators (e.g., study quality) that explain heterogeneity among studies. A systematic search was conducted across four databases from January 1 st , 2020 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 151 publications
(184 reference statements)
2
63
1
3
Order By: Relevance
“…The mental health of parents with young children appears to have been particularly affected by the pandemic (Racine et al, 2022); indeed, having young children was identified as a risk factor for distress during the pandemic (Pierce et al, 2020). Although the triggers of mental distress for parents during the pandemic are diverse, and vary from family to family, commonly reported factors include fears of infection, financial and job insecurity, the demands of balancing work and childcare, disruptions to self-care routines, and low levels of social support (Calvano et al, 2021;Davidson et al, 2021;Racine et al, 2022;Russell et al, 2020).…”
Section: Parental Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The mental health of parents with young children appears to have been particularly affected by the pandemic (Racine et al, 2022); indeed, having young children was identified as a risk factor for distress during the pandemic (Pierce et al, 2020). Although the triggers of mental distress for parents during the pandemic are diverse, and vary from family to family, commonly reported factors include fears of infection, financial and job insecurity, the demands of balancing work and childcare, disruptions to self-care routines, and low levels of social support (Calvano et al, 2021;Davidson et al, 2021;Racine et al, 2022;Russell et al, 2020).…”
Section: Parental Mental Healthmentioning
confidence: 99%
“…The mental health of parents with young children appears to have been particularly affected by the pandemic (Racine et al, 2022); indeed, having young children was identified as a risk factor for distress during the pandemic (Pierce et al, 2020). Although the triggers of mental distress for parents during the pandemic are diverse, and vary from family to family, commonly reported factors include fears of infection, financial and job insecurity, the demands of balancing work and childcare, disruptions to self-care routines, and low levels of social support (Calvano et al, 2021;Davidson et al, 2021;Racine et al, 2022;Russell et al, 2020). It is well documented that parental mental health difficulties are a risk factor for early childhood difficulties with self-regulation and related executive functions, as well as difficulties with coping with negative emotions or stressful situations, which may either manifest as a tendency to be self-critical and anxious (i.e., internalizing difficulties) or a tendency to 'act out' in disruptive or aggressive ways (i.e., externalizing behavioural problems) (Carneiro et al, 2016;Power et al, 2021;Rigato et al, 2022;Ross et al, 2020;Stein et al, 2014;Sweeney & MacBeth, 2016).…”
Section: Parental Mental Healthmentioning
confidence: 99%
“…The lives of mothers have been notably disrupted by lack of childcare, supervising at-home learning, and caregiving of family members at risk of COVID-19 complications (Frank et al 2021 ; MCGoron et al 2021 ). In a meta-analysis of 18 studies of 8981 mothers of children under 5 years old during the first year of the pandemic, 26.9% (95% CI: 21.3–33.4) experienced clinically significant depressive symptoms and 41.9% (95% CI: 26.7–58.8) experienced anxious symptoms (Racine et al 2022 ). Several studies show large declines in mental health after the pandemic onset.…”
Section: Introductionmentioning
confidence: 99%
“…Few large studies have focused on mental health of mothers during the pandemic, and those that do are mostly cross-sectional or have a brief length of follow-up. Although there have been many longitudinal COVID-19 mental health studies (COVID-Minds Network 2021 ; Unnarsdóttir et al 2021 ), few focus on maternal mental health; all take place in Canada, Denmark, and the UK; and none specifically assess PPD history (Dickerson et al 2022 ; Ladekarl et al 2021 ; Overbeck et al 2022 ; Racine et al 2022 ; Saleem et al 2022 ; Zhang et al 2022 ). Only one Danish cohort examines symptom trajectories at multiple timepoints throughout the pandemic, and they found no differences (Overbeck et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…With schools and daycare centers closed, established daily routines disappeared and parents had to find new ways to combine childcare (including homeschooling), housework, and paid work (Global Gender Gap Index & World Economic Forum, 2021 ; Power, 2020 ). Thus, not surprisingly, research shows negative effects of the pandemic on families with young children (Gassman-Pines et al, 2020 ; Janssen et al, 2020 ; Patrick et al, 2020 ) versus older adults (Sterina et al, 2022 ) and on the well-being of parents (e.g., Cameron et al, 2020 ; Cusinato et al, 2020 ; Etheridge & Spantig, 2020 ; Harth & Mitte, 2020 ; Huebener et al, 2021 ; Racine et al, 2022 ).…”
mentioning
confidence: 99%